Towards Increasing the Utilization of Anaerobic Digestate from Biogas Production in Agrotechnologies - Tymchuk, Ivan; Malovanyy, Myroslav; Zhuk, Volodymyr; Kochubei, Viktoriya; Yatsukh, Katerina; Luchyt, Liubov (Ecological Questions, 2023)
The paper presents the results of a comprehensive study that focused on the composition and properties of digestate obtained through mesophilic anaerobic co-fermentation of broadleaf cattail suspensions with yeast waste inoculum. Additionally, bioindication studies were conducted to evaluate the effect of the digestate on the germination of ryegrass and barley under lab-scale conditions. The initial total solids in suspensions before digestion varied from 5%wt. to 10%wt., and the mass fraction of the inoculum ranged from 0.05 to 0.2. Through thermogravimetric analysis, it was observed that digestate samples with higher initial inoculum content exhibited lower thermal stability. One of the limiting factors for the use of digestate was its high water content, ranging from 95.6% to 97.9%. To address the high water content, centrifugation of the digestate samples was performed for 2 minutes at 5000 rpm. This process led to significant dewatering, particularly for samples with a higher inoculum content. The maximum possible reduction in water content of the digestate was achieved at 31.65%. The bioindication study involved evaluating the germination of ryegrass and barley in soil samples with different digestate content. The results indicated that the highest germination rates were achieved with a digestate content of 20%wt. For ryegrass, the germination rate was 93.33%, which was 1.67% higher than the soil control sample and 0.33% higher than the sterile control. Similarly, for barley, the germination rate was 91.33%, surpassing the soil control by 4.00% and the sterile control by 0.67%. The findings of this study confirm the potential of utilizing digestate in agricultural technologies as an additional source of plant nutrients. The comprehensive analysis of the digestate's composition, properties, and its positive impact on germination rates further supports its viability as a valuable resource in agricultural practices.